2003
DOI: 10.1128/aem.69.6.3244-3250.2003
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Reserve Material Poly-β-Hydroxybutyrate inAzospirillum brasilenseStress Endurance and Root Colonization

Abstract: When grown under suboptimal conditions, rhizobacteria of the genus Azospirillum produce high levels of poly-␤-hydroxybutyrate (PHB). Azospirillum brasilense strain Sp7 and a phbC (PHB synthase) mutant strain in which PHB production is impaired were evaluated for metabolic versatility, for the ability to endure various stress conditions, for survival in soil inoculants, and for the potential to promote plant growth. The carbon source utilization data were similar for the wild-type and mutant strains, but the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 40 publications
(43 reference statements)
5
115
0
1
Order By: Relevance
“…Though reports regarding the survivability of Methylobacterium strains subjected to different stress responses are scarce, we believe that the enhanced survivability of Methylobacterium strains may be attributed to the high EPS production and PHB production under increased carbon concentration in the growth medium. The role of high carbon concentration in aggregation of bacterial strains such as Azospirillum, Azotobacter, and Pseudomonas and the concomitant accumulation of high levels of intracellular storage substances such as polyhydroxyalkanoates (PHA) has been reported by numerous workers (Burdman et al, 1998;Burdman et al, 2000;Kadouri et al, 2003;Madi and Henis, 1989). Results of our present study go well with the findings of Ayub et al (2004), who correlated high stress tolerance efficiency in Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Though reports regarding the survivability of Methylobacterium strains subjected to different stress responses are scarce, we believe that the enhanced survivability of Methylobacterium strains may be attributed to the high EPS production and PHB production under increased carbon concentration in the growth medium. The role of high carbon concentration in aggregation of bacterial strains such as Azospirillum, Azotobacter, and Pseudomonas and the concomitant accumulation of high levels of intracellular storage substances such as polyhydroxyalkanoates (PHA) has been reported by numerous workers (Burdman et al, 1998;Burdman et al, 2000;Kadouri et al, 2003;Madi and Henis, 1989). Results of our present study go well with the findings of Ayub et al (2004), who correlated high stress tolerance efficiency in Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 82%
“…Stress endurance experiments were carried out according to Kadouri et al (2003) with a slight modification. For each experiment the initial number of bacterial cells was maintained higher than 9 log cfu mL -1 .…”
Section: Stress Endurance Efficiency Under Different Induced Stress Cmentioning
confidence: 99%
“…Probably relevant to the storage function, it has been shown that PHA accumulation improves bacterial tolerance to high temperature, exposure to reactive oxygen species, osmotic stress, UV irradiation, desiccation, and other environmental stresses (29). In the symbiotic context, PHA granules have been identified in rhizobial cells.…”
Section: Host Fitness Is Negatively Affected By Infection With Symbiontmentioning
confidence: 99%
“…Por outro lado, as características celulares que indicam a rizocompetência, mesmo que pouco exploradas pela literatura, podem se apresentar comuns entre diferentes espécies microbianas permitindo seu estudo de maneira comparativa (BASHAN e DE-BASHAN, 2005;MARASCO et al, 2012). Muitas das substâncias presentes na formulação do meio de cultura serão utilizadas pelas estirpes inoculantes como base para a biossíntese de biomoléculas de extrema importância para a qualidade dos inoculantes produzidos, como exopolissacarídeos e lipopolissacarídeos (OKON; ITZIGSOHN, 1992;BURDMAN et al, 2000;KADOURI;BAHAT-SAMET;CASTRO-SOWINSKI;OKON, 2004). Estes polímeros possuem grande importância para desenvolvimento de formulações inoculantes de alta qualidade, atuando como fator de proteção das células microbianas contra a dissecação e facilitando sua adesão a superfícies, melhorando a viabilidade e rizocompetência das formulações (HUNGRIA et al, 2005;MALUSÁ et al, 2012).…”
Section: Inoculantes Agrícolas Para Plantas Não Leguminosas: Biofertiunclassified